BiI3 nucleation and coalescence onto amorphous substrates - Aguiar, Ivana; Fornaro, Laura (Scientia Plena, 2011)
BiI3 nucleation and coalescence was performed onto glass substrates. Further film growth onto the best nucleated layers were then made, with the objective of using these films as detectors for digital imaging. BiI3 was synthesized from Bi2O3CO2.H2O y KI, and then treated with HI to avoid the formation of BiOI by hydrolysis. The material was purified by zone melting followed by two sublimations. Nucleations were performed by physical vapor deposition (PVD) on 2”x2” glass substrates with an initial pressure of 4 x 10-3 Pa. Source and substrate were electrically heated, with temperatures ranging from 150-180 ºC and 50-150 ºC for source and substrate respectively, in order to study supersaturation influence on nucleation. The obtained nuclei were between 0.2 to 0.03 μm in size. Annealing was performed seeking for nuclei coalescence, heating them at 80-110 ºC during 5 days. Coalescence was only observed when annealing the smallest nuclei (sizes between 0.03 and 0.05 μm). Optical microscopy shows that nuclei coalescence giving rounded and highly oriented microcrystals, about 100 times larger in size than the original nuclei. Nuclei coalescence was found to increase with annealing time and temperature. Further growth of BiI3 films was performed onto the best nucleated and coalesced layers. These films were characterized by optical microscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). Results are very promising; however, microcrystals do not have a preferred orientation as is desirable for using them for the final application they are intended for. Future work will be conducted to improve nucleation and coalescence seeking for uniformity as far as the best orientation for such final application, that means, for ionizing radiation digital imaging.